Evaluation of the Effectiveness of a Clinical Pathway Based on Interprofessional Collaboration in the Treatment of Acute Heart Failure - Wasliati , balqis (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Acute heart failure is a medical emergency that requires a multidisciplinary approach to improve patient outcomes. An interprofessional collaboration-based Clinical Pathway has been implemented as a strategy to enhance treatment effectiveness, accelerate clinical decision-making, and reduce care variation. This study aims to evaluate the effectiveness of implementing an interprofessional collaboration-based Clinical Pathway in the management of acute heart failure in hospitals. This research uses a literature review approach by analyzing various recent journals discussing Clinical Pathway and acute heart failure management. The study results show that the implementation of Clinical Pathway can improve treatment efficiency, reduce complications, and accelerate patient recovery time. In conclusion, the integration of an interprofessional collaboration-based Clinical Pathway is an effective approach to improving the quality of care for patients with acute heart failure. This research method uses a retrospective cohort study approach with analysis of medical record data from patients treated in the last five years. The study population consisted of patients diagnosed with acute heart failure, with sample selection carried out using a purposive sampling method. Data collected includes length of stay, complication rates, compliance with clinical guidelines, and level of patient satisfaction. Data analysis was carried out with descriptive and inferential statistics using the chi-square test and logistic regression. The research results show that implementingthe Clinical Pathway can increase treatment efficiency, reduce complication rates, and speed up patient recovery time. Implementation of the Clinical Pathway also has a positive impact on health workers' compliance with standard therapy guidelines and improves communication and coordination between health professionals in patient management. Additionally, patients treated with Clinical Pathway reported higher levels of satisfaction compared to the control group who received conventional care.